Solution plasma: new synthesis method of N-doped carbon dots as ultra-sensitive fluorescence detector for 2, 4, 6-trinitrophenol. (28th September 2020) - Kim, Kyusung; Chokradjaroen, Chayanaphat; Saito, Nagahiro
Abstract: Herein, we report the synthesis of nitrogen-doped carbon dots (NCDs) through solution plasma (SP) for the first time. The SP method occurs a rapid dissociation of molecules, such as organic compounds, caused by an electrical discharge between electrodes immersed in a solution. The dissociation can result in the creation of various radicals such as ·C2, ·CN, and ·H which enable the rapid synthesis of carbon dots (CDs). The unique reaction of radicals allowed the formation of CDs with high N concentration and functionalization of the surface in a short time. In this study, by using the SP method, a very fine NCDs with size of 6 nm were synthesized from a pyridine/water mixture in just 10 min. Bright blue fluorescence (410 nm) with a high quantum yield (61%) was observed due to the high N concentration and the surface passivation. From the potential application point of view, the synthesized NCDs showed an excellent detection property for 2, 4, 6-trinitrophenol (TNP) by fluorescence quenching effect. It was due to rich amino-functional groups which act as a reaction pathway to TNP. This phenomenon was caused by the synergetic effect of a photo-induced electron transfer with the assistance of proton transfer-assisted electron transfer.